Bioactive compounds of ethanol extract from agarwood leaves (Aquilaria malaccensis) and antimicrobial activity against bacteria and fungi growing on the skin - Ridwanti Batubara; BASUKI WIRJOSENTONO; AMIR HAMZAH SIREGAR; URIP HARAHAP; TAMRIN TAMRIN (Society for Indonesian Biodiversity, 2021)
Abstract. Batubara R, Wirjosentono B, Siregar AH, Harahap U, Tamrin. 2021. Bioactive compounds of ethanol extract from agarwood leaves (Aquilaria malaccensis) and antimicrobial activity against bacteria and fungi growing on the skin. Biodiversitas 22: 2884-2890. Agarwood plants (Aquilaria malaccensis Lamk.) provide numerous benefits and have been cultivated by the people. The leaves containing various compounds, such as flavonoids, glycosides, triterpenoids and tannins with antibacterial and antifungal activities, were reported to be potential for flesh wound healing. Therefore, research on these activities against microorganisms that cause infection in wounds was carried out in vitro. This research aims to determine the antibacterial and antifungal activities of agarwood leaves ethanol extract against three bacteria species (Staphylococcus epidermidis, Staphylococcus aureus, and Propionibacterium acnes) and two fungi species (Candida albicans and Trichophyton sp.) that commonly cause skin infection. The results of this research show that the concentration of ethanol extract of agarwood leaves affected the bacterial and fungal growth inhibition zone’s diameter. The best inhibitory potential occurred at 5% concentration in activity against bacteria and fungi. The extract’s active compounds contributing to the antimicrobial activity were the flavonoids and tannins. Furthermore, GC-MS identification shows that the ethanol extract from agarwood leaves contained Disulfide, dioctyl; 6,7-Dimethylquinoxaline; (E)-1,3-Di-m-tolylallyl ethyl Carbonate; 5-(2-Methoxyphenyl)-1,2-dihydropyrazol-3-one; 9-[(tert-Butyldimethylsilyl)oxy]benzo[3,4]cyclod ec-3-ene-1,5-diyne; Neophytadiene, 2-Hexadecen-1-ol, 3,7,11,15-tetramethyl-, [R-[R*,R*-(E)]]-; Hexadecanoic acid, methyl ester and a-(3-chloro-4-hydroxyphenyl)-aphenoxy-a-phenyl acetonitrile